Experimental and Numerical Research on Seismic Performance of Earthquake-Damaged RC Frame Strengthened with CFRP Sheets - Lai Wang; Wei Xuan; Ying Zhang; Shuping Cong; Feng Liu; Qiumei Gao; Haitao Chen (Advances in Materials Science and Engineering)
In order to assess the seismic performance of damaged reinforced concrete (RC) frame strengthened with carbon fiber reinforced polymers (CFRP) sheets, two experimental specimens with identical reinforcement ratio and geometric dimensions were designed following Chinese code for seismic design of buildings. Experimental specimens consist of a reference (undamaged) RC frame, namely, KJ-1, and an earthquake-damaged RC frame strengthened with CFRP sheets, namely, KJ-2. A pseudostatic test was conducted on the two specimens to simulate moderate earthquake damage. The strengthening effects of CFRP sheets on damaged RC frame were discussed in terms of hysteretic curve, skeleton curve, stiffness degradation, and ductility. In addition, numerical method based on fiber model method was utilized to analyze the seismic performance of KJ-1 and KJ-2 and it is compared with the experimental result. Both the results confirm that the method of exterior bonding CFRP sheets on the damaged RC frame has restored the seismic performance such as bearing capacity, stiffness, and ductility to its original undamaged level, and some of the seismic performance of the damaged RC frame strengthened with CFRP sheets is even better than the undamaged one, which proves that the method has significant effect in strengthening postearthquake-damaged RC frames.